Financial Constraints and Moral Hazard: The Case of Franchising - Fan, Ying; Kühn, Kai-Uwe; Lafontaine, Francine (Journal of Political Economy, 2017)
Financial constraints are considered an important impediment to growth for small businesses. We study theoretically and empirically the relationship between the financial constraints of agents and the organizational decisions and growth of principals, in the context of franchising. We find that a 30 percent decrease in average collateralizable housing wealth in an area is associated with a delay in chains’ entry into franchising by 0.33 year on average, or 10 percent of the average waiting time, and a reduction in chain growth and hence a reduction in franchised chain employment of about 9 percent.